BRICS na América Latina e Caribe: a emergência de uma nova governança global - (:unkn) unknown (Universidade Federal do Pampa, 2016)
This paper aims to analyze the role of BRICS in its proposal for reform in global governance, highlighting the projection of the group in Latin America and the Caribbean. To do so, the work establishes a historical and theoretical approach to the formation of the Third World and, therefore, of the movements characterized as South-South Cooperation, so as to understand the conditions that contributed to the emergence of the BRICS in the 21st century. Furthermore, the study analyzes the ongoing process of formation and consolidation of the bloc, reflecting on its proposals and, above all, its role in projecting a supposed reform in global "post-neoliberal" governance. It is argued that in a scenario of transformations of the international system, the BRICS has invested in the sum of efforts to defend the demands of developing countries in the global governance spheres, given the inability of traditional powers to manage economic and financial stability in the international environment. This work also seeks to investigate, in this context, in which way the commercial and financial relations between BRICS and Latin America and the Caribbean have been established. To this end, the role of Brazil will be highlighted, especially with regards to its role within both groups of countries. Finally, it is intended to verify the existence of reciprocity of relations between the bloc and the Latin American region, evaluating the role of Brazil in the construction of this type of relationship favorable to both countries.
BRICS in Latin America and the Caribbean: the emergency of a new global governance abstract
Keywords: BRICS; Relações internacionais: Brasil; Cooperação internacional; Bloco econômico; América Latina; Caribe; Neoliberalismo; International relations: Brazil; International cooperation; Trade bloc; Latin America; Caribbean; BRICS; CNPQ::CIENCIAS SOCIAIS APLICADAS